Accountancy and financial management (SYBCom) - Chopde L.N., Choudhari P.H., Mehta D.H., Gandhi Kishor & others (Sheth Publ. Mumbai, 2004)
Commerce
ENGLISH
Keywords: Accountancy and financial management (SYBCom); Commerce; Commerce